HPMA-Based Polymer Conjugates for Repurposed Drug Mebendazole and Other Imidazole-Based Therapeutics - Studenovský, Martin; Rumlerová, Anna; Kostka, Libor; Etrych, Tomáš (Polymers, 2021)
Recently, the antitumor potential of benzimidazole anthelmintics, such as mebendazole and its analogues, have been reported to have minimal side effects, in addition to their well-known anti-parasitic abilities. However, their administration is strongly limited owing to their extremely poor solubility, which highly depletes their overall bioavailability. This study describes the design, synthesis, and physico-chemical properties of polymer-mebendazole nanomedicines for drug repurposing in cancer therapy. The conjugation of mebendazole to water-soluble and biocompatible polymer carrier was carried out via biodegradable bond, relying on the hydrolytic action of lysosomal hydrolases for mebendazole release inside the tumor cells. Five low-molecular-weight mebendazole derivatives, differing in their inner structure, and two polymer conjugates differing in their linker structure, were synthesized. The overall synthetic strategy was designed to enable the modification and polymer conjugation of most benzimidazole-based anthelmintics, such as albendazole, fenbendazole or albendazole, besides the mebendazole. Furthermore, the described methodology may be suitable for conjugation of other biologically active compounds with a heterocyclic N-H group in their molecules.
Keywords: drug delivery; polymer; drug repurposing; controlled release; mebendazole; HPMA